ANALISIS PENERAPAN LIVE STREAMING YOUTUBE SUSKA TV SEBAGAI MEDIA ALTERNATIF TELEVISI KAMPUS - Mutia, Tika (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2022)
The advances in communication technology that is so dynamic in the all-digital era now also penetrated the television media. Many platforms use the internet to reach a wider audience. No exception on-campus community television such as Suska TV using the Youtube account "Suska TV Official" took part in providing information to the campus community. The purpose of this study was to determine the extent of internet-based live streaming video into alternative communication media at Suska TV as campus television. The research uses an interpretive paradigm with a qualitative method and case study approach. Data collection techniques using observation, in-depth interviews, and online search. The results found 3 factors utilizing live streaming video using virtual mixer technology and internet networks in Suska TV. First, it can generate live shows anywhere. Production of news broadcasts, campus programs, and events does not have to be done in Suska TV studios. Secondly, Following communication technology trends. Through a YouTube account, it gives freedom for the campus community to choose to watch the programs they want from their respective gadgets. Meanwhile, the inhibiting factors are the bandwidth needed in The UIN Suska Riau campus which still needs to be increased. This is needed for broadcast-quality to still maintain and isnâ€™t constrained by delays. Secondly, the qualification of the live streaming technology that is used must always keep up with existing developments. This requires a lot of money and Human Resources (HR) so that Suska TV can still actively carry out production through broadcast digitization.Keywords: Live Streaming, Youtube, Campus Television, Alternative Media Communication, Â Â